Perencanaan Pengolahan Limbah Air Wudhu di Masjid Al Mu’minin Kota Kendari dengan Menggunakan Filtrasi Sederhana - Pramoto, Muh. Anggi; Assiddieq, Moch.; Rosdiana, Rosdiana (Universitas Muhammadiyah Kendari, 2022)
The large number of Muslim populations in Indonesia cannot be separated from religious activities, one of which is prayer. Before performing prayers, a Muslim first performs ablution using water. With this activity, it will produce a large amount of wastewater in the Al-Mu'minin mosque itself, which can produce ablution water waste of 685.1 L/day with the results of laboratory tests carried out on the quality of groundwater pH 7.84, TSS 38.8 mg/L and turbidity. 6.40 NT in the analysis of the quality of ablution water waste showed that it had exceeded the quality standard, namely TSS 68 mg/L and turbidity was 5 NTU, while the analysis of filtered ablution water waste showed a decrease in levels, namely pH 7.55, TSS 18.70 mg/L and turbidity 3.18 NTU. From the calculation results, the volume of wastewater produced by the mosque is 0.6851 m3/day using a treatment unit in the form of an initial sedimentation tank which has a volume size (Length = 84 cm, Width = 76 cm and Height = 101 cm), a simple filter using media in the form of (Gravel, Sand, Palm Fibers, Charcoal and Sponge) each has a height of 15 cm and the final reservoir has a volume (Length = 84 cm, Width = 76 cm and Height = 101 cm).